2014
DOI: 10.1186/1746-1596-9-123
|View full text |Cite
|
Sign up to set email alerts
|

Silencing BMP-2 expression inhibits A549 and H460 cell proliferation and migration

Abstract: BackgroundBone morphogenetic protein 2 (BMP-2) is a member of the TGF-β superfamily that is closely correlated with many malignancies, particularly lung cancer. However, the effects of silenced BMP-2 on lung cancer cell proliferation and migration are not clear.MethodsUsing quantitative real-time RT-PCR, BMP-2 mRNA expression was detected in 61 non-small cell lung cancer (NSCLC) samples. Survival curves were generated using follow-up data. Relationships between clinical or pathological characteristics and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
20
1
Order By: Relevance
“…GSC‐MSCs differ from LC‐MSC, which could not restore GSC1 cancer cell growth capacity, not only in their capacity to secrete HGF but also in their capacity to express a panel of differentiation regulatory genes which are involved in enhancing cell proliferation and migration. Among others, these include BMP2 which induces bone and cartilage formation and has a role in cell proliferation and migration ; GDF6 and GDF15 growth differentiation factors which are regulators of tissue differentiation and maintenance ; MCAM, melanoma cell adhesion molecule (CD146), whose expression in mesenchymal stem cells is associated with their vascular smooth muscle commitment and PPARG, peroxisome proliferator‐activated receptor gamma, which is a regulator of adipocyte differentiation . This panel of MSC specific genes whose expression is elevated in GSC‐MSC implicates increased potency of enhancing pro‐tumorigenic activity in this specific gastric carcinoma tumor by stimulating the growth, migration, and invasion of GSC1 epithelial cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…GSC‐MSCs differ from LC‐MSC, which could not restore GSC1 cancer cell growth capacity, not only in their capacity to secrete HGF but also in their capacity to express a panel of differentiation regulatory genes which are involved in enhancing cell proliferation and migration. Among others, these include BMP2 which induces bone and cartilage formation and has a role in cell proliferation and migration ; GDF6 and GDF15 growth differentiation factors which are regulators of tissue differentiation and maintenance ; MCAM, melanoma cell adhesion molecule (CD146), whose expression in mesenchymal stem cells is associated with their vascular smooth muscle commitment and PPARG, peroxisome proliferator‐activated receptor gamma, which is a regulator of adipocyte differentiation . This panel of MSC specific genes whose expression is elevated in GSC‐MSC implicates increased potency of enhancing pro‐tumorigenic activity in this specific gastric carcinoma tumor by stimulating the growth, migration, and invasion of GSC1 epithelial cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BMP2 is over-expressed in all subtypes of NSCLC and contributes to tumor cell proliferation and migration [17,24]. In this study, we examined the mRNA levels of BMP3, BMP4, BMP5, BMP6, BMP7, BMP10, and BMP13 in the NSCLC tissues and the corresponding noncancerous tissues by qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BMP2 is expressed as a sensitive marker in various human cancers, including glioma, ovarian, salivary adenocarcinoma, and pancreatic cancer, whereas BMP7 is most frequently expressed in breast cancer and up-regulated in melanoma and metastases of malignant melanoma [10][11][12][13][14][15]. In addition, it has been shown that BMP2 is highly expressed in NSCLC and small-cell lung carcinoma (SCLC) cell lines to promote cell migration and invasion, correlating with poor survival of patients with advanced NSCLC [16,17], while the expression of BMP3 and BMP6 is down-regulated in NSCLC tissues and cell lines, which is due to aberrant DNA hypermethylation in the promoters of BMP3 and BMP6 genes and is associated with lung tumor development [18,19]. It is currently unclear whether other BMPs are associated with NSCLC progress.…”
Section: Introductionmentioning
confidence: 99%
“…found that BMP-2 could enhance the motility and invasiveness of colon cancer cells through up-regulation of cancer stem cells (CSCs) and played an important role in the metastasis of colon cancer. BMP-2 knockdown in lung cancer cell lines A549 and H460 suppressed their proliferation and migration8. BMP2/BMPR axis triggered Epithelial mesenchymal transition (EMT) process in gastric cancer, and then was involved in tumor cell migration, invasion and metastasis via the activation of PI3K/AKT and MEK/ERK pathways9.…”
Section: Discussionmentioning
confidence: 99%